Perfluoropolyether oil-based magnetic fluid and preparation method thereof
By using chemical co-precipitation method of nano-Fe3O4 magnetic particles and fluorocarbonized structural modification technology in fluoroether oil-based magnetic fluid, the problem of insufficient dispersion and settlement resistance of magnetic powder is solved, and efficient magnetic fluid dispersion and saturation magnetization are achieved. Improvement meets the sealing needs in corrosive environments.
Patent Information
- Application Number
- CN202411651109.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
The existing fluoroether oil-based magnetic fluids have shortcomings in terms of magnetic powder dispersion and settlement resistance, and cannot effectively meet the sealing needs in corrosive environments.
NanoFe3O4 magnetic particles were prepared by chemical coprecipitation method, and the nanomagnetic particles were uniformly dispersed in perfluoropolyether oil by fluorocarbonization structure modification and double-bridge connection method, thereby improving the stability of the magnetic fluid and saturation magnetization.
It significantly improves the dispersion and sink resistance of magnetic fluids in corrosive environments, enhances its saturation magnetization, and meets the sealing needs of high temperature and high corrosion.
Smart Images

Figure CN119480324A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic fluids, and in particular to a perfluoropolyether oil-based magnetic fluid and a preparation method thereof. Background Art
[0002] Modern machinery, information, chemical and other industrial production equipment are all intelligent and automated equipment. These equipments are highly precise, require few people and have a high degree of automation, but these equipments have a common feature, that is, they require a large number of rotating parts and hydraulic equipment inside, which leads to a problem of sealing. Leakage problems caused by mechanical seal failure are endless. Once this problem occurs, it will cause production stagnation, equipment damage and product quality decline. In severe cases, harmful substances leak and pollute the environment, and even endanger human health or life. Magnetic fluid is a stable colloidal solution system composed of nano-scale magnetic particles, surfactants and base carrier fluids. Magnetic fluid has many unique properties, such as magnetic viscosity, magneto-optical properties, magnetocaloric properties, etc. Therefore, it is widely used in many fields, such as sealing, lubrication, grinding, heat transfer, dampers, sensors and medical instruments. Among them, the advantages of magnetic seals are zero leakage, low wear and low operating temperature. Therefore, in the field of rotating seals, magnetic fluid seals have great advantages over traditional mechanical seals.
[0003] At present, the main magnetic fluids used in magnetic fluid seals include diester-based magnetic fluids, kerosene-based magnetic fluids, hydrocarbon-based magnetic fluids, etc. However, these magnetic fluids have a narrow operating temperature range and can only seal air but not active gases that are corrosive to acids and alkalis. Fluoroether oil-based magnetic fluids have superior properties such as high thermal stability, extremely high oxidation stability, excellent chemical inertness, strong corrosion resistance, good lubrication performance, and high decomposition temperature. The magnetic fluid is applied to corrosive environments, especially in corrosive gas and liquid sealing. It has unparalleled advantages over traditional sealing magnetic fluids. However, the current fluoroether oil-based magnetic fluids, the dispersibility of magnetic powder in fluoroether oil, and the anti-sedimentation properties of magnetic fluids still need to be improved.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first object of the present invention is to provide a method for preparing a perfluoropolyether oil-based magnetic fluid, using a fluorinated structure-modified nano-Fe 3 O 4 Magnetic particles are used as magnetic cores, and double bridge connection method is adopted to make nano-Fe 3 O 4 The magnetic particles are evenly dispersed in the perfluoropolyether oil to improve the stability of the magnetic fluid and 3 O 4Under the same content, the saturation magnetization intensity of fluoroether oil-based magnetic fluid can be improved.
[0006] The second object of the present invention is to provide a perfluoropolyether oil-based magnetic fluid, which is prepared by the above-mentioned preparation method of the perfluoropolyether oil-based magnetic fluid.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] A method for preparing a perfluoropolyether oil-based magnetic fluid comprises the following steps:
[0009] S1. Preparation of nano-Fe by chemical co-precipitation method 3 O 4 magnetic particles, after the reaction is completed, a first mixed material is obtained, the first mixed material is mixed with an antioxidant and oleic acid and reacted to obtain a second mixed material;
[0010] S2. The second mixture is mixed with a fluorinated surfactant and a perfluoropolyether carboxylic acid and reacted to obtain a third mixture, and the third mixture is extracted with an organic solvent for phase transfer to obtain an organic phase containing a nano-magnetic material;
[0011] S3. The organic phase containing the nano-magnetic material is mixed with a non-ionic fluorinated surfactant and a perfluoropolyether oil and reacted to obtain the perfluoropolyether oil-based magnetic fluid.
[0012] A perfluoropolyether oil-based magnetic fluid is prepared by the preparation method of the perfluoropolyether oil-based magnetic fluid described in the above embodiment.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] The present invention adopts nano-iron tetroxide as the core, and protects the lattice structure and prevents agglomeration by coating the surface with an antioxidant and oleic acid. In order to improve the affinity between the magnetic powder and the fluoroether oil, perfluoropolyether carboxylic acid is used to perform fluorocarbon grafting modification on the nano-iron tetroxide particles. However, due to the poor mutual solubility of oleic acid and perfluoropolyether carboxylic acid, it is difficult to coat. The present invention adopts a fluorine surfactant as a first bridging agent, which can combine the perfluoropolyether carboxylic acid on the surface of the oleic acid, and then uses a non-ionic fluorinated surfactant as a second bridging agent to improve the binding force between the perfluoropolyether carboxylic acid and the perfluoropolyether oil, so that the fluorocarbon grafted magnetic particles are uniformly dispersed in the perfluoropolyether oil, thereby improving the magnetic Fe 3 O 4 The dispersibility in fluoroether oil improves the anti-settling property and saturation magnetization intensity of magnetic fluid.
[0015] The overall structure of the perfluoropolyether oil-based magnetic fluid prepared by the method of the present invention is a three-dimensional grid structure with nano-ferroferric oxide as nodes, surfactant as links and perfluoropolyether oil as a frame. The perfluoropolyether oil-based magnetic fluid with this structure has excellent chemical stability, antioxidant stability and thermal stability, and the magnetic ferroferric oxide has good dispersibility in the base oil, excellent anti-settling property and high saturation magnetization. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 TEM image of the fluoroether oil-based magnetic fluid in Example 1 of the present invention;
[0018] Figure 2 is the XRD pattern of the fluoroether oil-based magnetic fluid in Example 1 of the present invention;
[0019] Figure 3 is an infrared image of the fluoroether oil-based magnetic fluid in Example 1 of the present invention;
[0020] Figure 4 : is a VSM diagram of the fluoroether oil-based magnetic fluid in Example 1 of the present invention;
[0021] Figure 5 TEM image of the fluoroether oil-based magnetic fluid in Example 2 of the present invention;
[0022] Figure 6 is the XRD pattern of the fluoroether oil-based magnetic fluid in Example 2 of the present invention;
[0023] Figure 7 is an infrared image of the fluoroether oil-based magnetic fluid in Example 2 of the present invention;
[0024] Figure 8 : is a VSM diagram of the fluoroether oil-based magnetic fluid in Example 2 of the present invention;
[0025] Fig. 9 TEM image of the fluoroether oil-based magnetic fluid in Example 3 of the present invention;
[0026] Fig.10 is the XRD pattern of the fluoroether oil-based magnetic fluid in Example 3 of the present invention;
[0027] Fig.11 is an infrared image of the fluoroether oil-based magnetic fluid in Example 3 of the present invention;
[0028] Fig.12 : is a VSM diagram of the fluoroether oil-based magnetic fluid in Example 3 of the present invention;
[0029] Fig.13 This is a physical picture of the fluoroether oil-based magnetic fluid in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0031] The first aspect of the present invention provides a method for preparing a perfluoropolyether oil-based magnetic fluid, comprising the following steps:
[0032] S1. Preparation of nano-Fe by chemical co-precipitation method 3 O 4 magnetic particles, after the reaction is completed, a first mixed material is obtained, the first mixed material is mixed with an antioxidant and oleic acid and reacted to obtain a second mixed material;
[0033] S2. The second mixed material is mixed with a fluorine surfactant and a perfluoropolyether carboxylic acid and reacted to obtain a third mixed material, and the third mixed material is extracted with an organic solvent for phase transfer to obtain an organic phase containing a nano-magnetic material;
[0034] S3. The organic phase containing the nano-magnetic material is mixed with a non-ionic fluorinated surfactant and a perfluoropolyether oil and reacted to obtain a perfluoropolyether oil-based magnetic fluid.
[0035] The method of the present invention is to 3 O 4 The surface coating of antioxidant can protect the lattice structure of ferroferric oxide magnetic material to remain intact for a long time, and the coating of oleic acid can prevent agglomeration. Perfluoropolyether carboxylic acid is usually used in traditional fluoroether oil magnetic fluid to protect Fe 3 O 4 The surface of the particles is grafted to enhance the affinity between the magnetic powder and the perfluoropolyether oil. However, for the Fe 3 O 4Due to the poor mutual solubility of oleic acid and perfluoropolyether carboxylic acid, it is difficult to coat the perfluoropolyether carboxylic acid directly after coating the oleic acid. To solve this problem, the present invention uses a fluorinated surfactant as a first bridging agent, one end of which is connected to oleic acid and the other end is connected to perfluoropolyether carboxylic acid. The fluorinated surfactant is used as a bridge to coat the perfluoropolyether carboxylic acid on the Fe2O3 coated with oleic acid. 3 O 4 The particles are then coated with the magnetic powder to improve the affinity between the magnetic powder and the base oil, thereby increasing the nano-magnetic Fe 3 O 4 The dispersion of the particles in the base oil is then enhanced by using a nonionic fluorinated surfactant as the second bridging agent to further enhance the binding force between the perfluoropolyether carboxylic acid and the perfluoropolyether oil, making the nanomagnetic Fe 3 O 4 The particles can be stably and evenly dispersed in the perfluoropolyether oil, improving the anti-settling property and saturation magnetization intensity of the perfluoropolyether oil-based magnetic fluid. Fig.13 , which is a physical picture of the fluoroether oil-based magnetic fluid provided in an embodiment of the present invention.
[0036] In some specific embodiments of the present invention, the antioxidant used includes at least one of N-isopropyl-N-phenyl-p-phenylenediamine, N-phenyl-β-naphthylamine, and N-N'-diphenyl-p-phenylenediamine.
[0037] In some specific embodiments of the present invention, the fluorosurfactant used includes at least one of MS-7163 fluorosurfactant, MS-7100 fluorosurfactant, and TSF403 fluorosurfactant. The above fluorosurfactants can be combined with oleic acid and perfluoropolyether carboxylic acid, and can achieve a good bridging effect.
[0038] In some specific embodiments of the present invention, the perfluoropolyether carboxylic acid used includes at least one of a perfluoropolyether carboxylic acid with a molecular weight of 1000, a perfluoropolyether carboxylic acid with a molecular weight of 1500, and a perfluoropolyether carboxylic acid with a molecular weight of 2000.
[0039] In some specific embodiments of the present invention, the nonionic fluorinated surfactant used includes at least one of FC-403 nonionic fluorinated surfactant, FC-4430 nonionic fluorinated surfactant, and FC5504 nonionic gemini fluorocarbon surfactant. The above nonionic fluorinated surfactant can not only serve as a bridge connecting perfluoropolyether carboxylic acid and perfluoropolyether oil to improve dispersibility, but also has an antioxidant effect.
[0040] In some specific embodiments of the present invention, the perfluoropolyether oil comprises at least one of a 1000 molecular weight perfluoropolyether oil, a 1500 molecular weight perfluoropolyether oil, and a 2000 molecular weight perfluoropolyether oil.
[0041] In some specific embodiments of the present invention, in step S1, a chemical coprecipitation method is used to prepare nano-Fe 3 O 4 The magnetic particles include the following steps:
[0042] The aqueous solution containing divalent iron salt and trivalent iron salt is mixed with a precipitant under stirring, and an inert gas is introduced to perform oxygen removal protection. The stirring is continued until the reaction is completed to obtain a first mixed material. The stirring speed is 400-500r / min, for example, it can be any point value among 400r / min, 420r / min, 440r / min, 450r / min, 460r / min, 480r / min, 500r / min, or a range value consisting of any two point values.
[0043] In some specific embodiments of the present invention, the precipitant comprises aqueous ammonia and / or sodium hydroxide solution.
[0044] In some specific embodiments of the present invention, the molar ratio of the divalent iron salt to the trivalent iron salt is 1:1.9-2.1, for example, it can be any point value among 1:1.9, 1:1.95, 1:2, 1:2.05, 1:2.1 or a range value consisting of any two point values.
[0045] In some specific embodiments of the present invention, the prepared nano-Fe 3 O 4 The particle size of the magnetic particles is 10-30nm. The nano-Fe prepared by the method of the present invention 3 O 4 The magnetic particles have uniform particle size distribution.
[0046] In some specific embodiments of the present invention, in step S1, the step of obtaining the second mixed material includes: adding the antioxidant to the first mixed material in 4-6 times, stirring and reacting for 4-6 minutes, heating to 80-90°C, adding oleic acid, and continuing to stir and react for 4-6 minutes to obtain the second mixed material.
[0047] In some embodiments, typically but not limiting, for example, the antioxidant can be added in 4, 5 or 6 times; the stirring reaction time after adding the antioxidant can be any point value among 4min, 5min, 6min or a range value consisting of any two points; the reaction temperature with oleic acid can be any point value among 80°C, 83°C, 85°C, 87°C, 90°C or a range value consisting of any two points; the stirring reaction time after adding oleic acid can be any point value among 4min, 5min, 6min or a range value consisting of any two points.
[0048] In some embodiments of the present invention, Fe 3 O 4The mass ratio of magnetic particles, antioxidant and oleic acid is 40-45:0.48-0.52:2.8-3.2, for example, it can be any point value among 40:0.48:2.8, 43:0.48:0.28, 43:0.5:3, 43:0.52:3.2, 45:0.52:3.2 or a range value consisting of any two point values.
[0049] In some specific embodiments of the present invention, in step S2, the step of obtaining the third mixed material includes: adding the fluorinated surfactant to the second mixed material in 3-5 times, stirring and reacting at 80-90°C for 2-3 minutes, then adding perfluoropolyether carboxylic acid, and continuing to stir and react for 30-35 minutes to obtain the third mixed material.
[0050] In some embodiments, typically but not limiting, for example, the fluorosurfactant can be added in 3, 4 or 5 times; the stirring reaction temperature when adding the fluorosurfactant can be any point value among 80°C, 83°C, 85°C, 87°C, 90°C, or a range value consisting of any two points; the stirring reaction time can be any point value among 2min, 2.5min, 3min, or a range value consisting of any two points; the stirring reaction time after adding the perfluoropolyether carboxylic acid can be any point value among 30min, 31min, 32min, 33min, 34min, 35min, or a range value consisting of any two points.
[0051] In some specific embodiments of the present invention, in step S2, the step of extracting phase transfer includes: adding cyclohexane to the third mixed material, stirring and mixing, pouring into a separating funnel and letting it stand, and taking the lower layer of black liquid to obtain an organic phase containing nanomagnetic materials.
[0052] The magnetic fluid is prepared by extractive phase transfer, which is different from the traditional method of preparing Fe 3 O 4 Compared with the method of preparing powder and dispersing it in base oil, the operation is simple and Fe 3 O 4 Better dispersibility in base oil.
[0053] In some specific embodiments of the present invention, in step S3, the process of mixing and reacting the organic phase containing the nanomagnetic material with the nonionic fluorinated surfactant and the perfluoropolyether oil specifically includes heating the organic phase containing the nanomagnetic material to 98-102°C at a stirring speed of 400-500r / min, adding the perfluoropolyether oil and stirring for 8-12min, heating to 120-125°C, adding the nonionic fluorinated surfactant in 3-5 times, stirring for 10-15min, and continuing to heat to 160-170°C and stirring for 20-30h. The stirring at 160-170°C has two functions: one is to enable the two surfactants to connect the nanomagnetic material and the perfluoropolyether oil, so that the nanomagnetic material is evenly and stably dispersed in the perfluoropolyether oil; the second is to fully remove the moisture wrapped inside the magnetic core.
[0054] In some embodiments, typically but not limiting, for example, in step S3, the reaction temperature when adding perfluoropolyether oil can be any point value among 98°C, 99°C, 100°C, 101°C, 102°C or a range value consisting of any two point values; the stirring reaction time after adding perfluoropolyether oil can be any point value among 8min, 9min, 10min, 11min, 12min or a range value consisting of any two point values; the reaction temperature when adding nonionic fluorinated surfactant can be 120°C, 121°C, 122°C, 123°C, 124°C, 125°C any point value in the range or any two point values in the range; the stirring reaction time after adding the non-ionic fluorinated surfactant can be any point value in the range of 10min, 11min, 12min, 13min, 14min, 15min or any two point values in the range; the temperature after further heating can be any point value in the range of 160℃, 162℃, 165℃, 168℃, 170℃ or any two point values in the range, and the stirring time can be any point value in the range of 20h, 22h, 24h, 26h, 28h, 30h or any two point values in the range.
[0055] In some specific embodiments of the present invention, the mass ratio of oleic acid, fluorine surfactant, perfluoropolyether carboxylic acid, nonionic fluorinated surfactant and perfluoropolyether oil is 2.8-3.2: 2.3-3.2: 10.6-21.2: 9.5-11.5: 60-70. Controlling the usage ratio within this range is beneficial to improving the nano-Fe 3 O 4 The dispersibility of magnetic materials in fluoroether oil improves the anti-settling property and specific saturation magnetization intensity of magnetic fluid.
[0056] In some specific embodiments of the present invention, in step S3, after the reaction is completed, an ultrasonic shear dispersion and separation step is further included, specifically including starting ultrasound at 160-170°C and ultrasonic shear dispersion at a speed of 7000-10000 r / min for 4-6 hours, reducing the speed to 400-500 r / min, cooling and placing on a magnet for 48-72 hours, and obtaining the perfluoropolyether oil-based magnetic fluid after centrifugal separation and filtration.
[0057] Ultrasonic shear dispersion is carried out in an ultrasonic constant temperature closed reactor. A high tangential speed and high frequency mechanical effect are generated by a new type of high-speed rotating Jieliu oblique corrugated gap working head. At the same time, the ultrasonic emulsification dispersion technology allows the material to experience strong ultrasound, high-speed soft shearing, extrusion and friction in a narrow gap to achieve a rapid and uniform dispersion effect. The present invention utilizes a dispersion technology that combines the high-speed shear emulsification technology generated by the new Jieliu oblique corrugated gap working head with the ultrasonic emulsification technology. The two work together to make the nano-Fe 3 O 4 The particles are evenly dispersed in the perfluoropolyether oil, avoiding the aggregation of multiple magnetic cores when dispersed in a high-viscosity carrier fluid, thereby improving the specific saturation magnetization intensity and anti-settling property of the fluoroether oil-based magnetic fluid.
[0058] Typically but not limiting, for example, the shear dispersion rotation speed can be any value among 7000r / min, 8000r / min, 9000r / min, 10000r / min, or a range consisting of any two values; the shear dispersion time can be any value among 4h, 4.5h, 5h, 5.5h, 6h, or a range consisting of any two values.
[0059] A second aspect of the present invention provides a perfluoropolyether oil-based magnetic fluid, which is prepared by the preparation method of the perfluoropolyether oil-based magnetic fluid described in any one of the aforementioned embodiments.
[0060] The perfluoropolyether oil-based magnetic fluid provided by the invention has excellent chemical stability, anti-oxidation stability and thermal stability, and the magnetic ferrosoferric oxide has good dispersibility in the base oil, excellent anti-settling property and high specific saturation magnetization intensity.
[0061] The following is a detailed description of some embodiments of the present invention in conjunction with specific examples. The raw materials used in the examples can be purchased from the market unless otherwise specified.
[0062] Example 1
[0063] Formula: 37.0g FeCl 2 ·4H 2 O; 100.0 g FeCl 3 6H 2O; 150ml ammonia water; 3g oleic acid; 2.3g MS-7163 fluorine surfactant; 10.6g 1000 molecular weight perfluoropolyether carboxylic acid; 65g 1000 molecular weight perfluoropolyether oil; 9.5g FC-403 nonionic fluorinated surfactant; 0.5g N-isopropyl-N-phenyl-p-phenylenediamine;
[0064] The preparation method comprises the following steps:
[0065] S1. Weigh 37.0g FeCl at room temperature 2 ·4H 2 O was dissolved in 60 ml of deionized water in a 100 ml beaker and set aside. 100.0 g of FeCl was weighed at room temperature. 3 6H 2 O in a 100ml beaker with 60ml deionized water for later use; measure 150ml ammonia water and put it in a 500ml three-necked bottle for later use; 2 Solution and FeCl 3 The solution was quickly mixed in a 200 ml beaker, and under a stirring condition of 450 r / min, the mixed solution was added into a three-necked bottle containing ammonia water in a uniform pouring manner within 1 minute, and nitrogen was introduced for oxygen protection. After stirring for 5 minutes, a first mixed material was obtained; 0.5 g of N-isopropyl-N-phenyl-p-phenylenediamine was added to the three-necked bottle containing the first mixed material in 4 portions, and the stirring reaction was continued for 5 minutes, and the temperature was raised to 85° C., and 3 g of oleic acid was added to the three-necked bottle at one time, and the stirring reaction was carried out for 5 minutes to obtain a second mixed material;
[0066] S2. Add 2.3g of MS-7163 fluorine surfactant to the three-necked bottle containing the second mixed material in four times, react at 85°C for 2min, add 10.6g of 1000 molecular weight perfluoropolyether carboxylic acid to the three-necked bottle in three times, stir and react for 30min to obtain the third mixed material. Then lower the temperature to room temperature, add 300ml of cyclohexane, stir for 10min, pour into a separating funnel and let stand for 24h, then take the lower layer of black liquid to obtain the organic phase containing nanomagnetic material;
[0067] S3. The organic phase containing the nanomagnetic material obtained in step S2 is placed in a 500mL three-necked flask, stirred at 450r / min and heated to 100°C, 65g of 1000 molecular weight perfluoropolyether oil is evenly added to the three-necked flask within 1min, stirred at 100°C for 10min, heated to 120°C, 9.5g of FC-403 nonionic fluorinated surfactant is added to the three-necked flask in three portions, stirred at 120°C for 10min, heated to 165°C, and stirred at this temperature for 20h; the black liquid is quickly transferred to an ultrasonic constant temperature sealed reactor, and ultrasonic and shear dispersion are started at 165°C, with an ultrasonic frequency of 20kHz, a power of 200W, and a shear speed of 7000r / min, and ultrasonic shear dispersion is performed in the ultrasonic constant temperature sealed reactor for 4 hours. The rotation speed was reduced to 400 r / min, and the temperature was naturally reduced to room temperature. The mixture was poured into a 250 ml beaker and placed on a magnet for 48 h. After centrifugation at a rotation speed of 5000 r / min for 30 min, the mixture was filtered using a 400-mesh filter cloth to obtain a brown-black fluoroether oil-based magnetic fluid.
[0068] Example 2
[0069] Formula: 37.0g FeCl 2 ·4H 2 O; 100.0 g FeCl 3 6H 2 O; 150ml ammonia water; 3g oleic acid; 3.2g MS-7100 fluorine surfactant; 15.9g 1500 molecular weight perfluoropolyether carboxylic acid; 65g 1500 molecular weight perfluoropolyether oil; 11.5g nonionic fluorinated surfactant FC-4430; 0.5g N-isopropyl-N-phenyl-p-phenylenediamine;
[0070] The preparation method comprises the following steps:
[0071] S1. Weigh 37.0g FeCl at room temperature 2 ·4H 2 O was dissolved in 60 ml of deionized water in a 100 ml beaker and set aside. 100.0 g of FeCl was weighed at room temperature. 3 6H 2 O in a 100ml beaker with 60ml deionized water for later use; measure 150ml ammonia water and put it in a 500ml three-necked bottle for later use; 2 Solution and FeCl 3The solution was quickly mixed in a 200 ml beaker, and under a stirring condition of 450 r / min, the mixed solution was added into a three-necked bottle containing ammonia water in a uniform pouring manner within 1 minute, and nitrogen was introduced for oxygen protection. After stirring for 5 minutes, a first mixed material was obtained; 0.5 g of N-isopropyl-N-phenyl-p-phenylenediamine was added to the three-necked bottle in 5 times, and the stirring reaction was continued for 5 minutes, and the temperature was raised to 85° C., and 3 g of oleic acid was added to the three-necked bottle at one time, and the stirring reaction was carried out for 5 minutes to obtain a second mixed material;
[0072] S2. Add 3.2g of MS-7100 fluorine surfactant to the three-necked bottle containing the second mixed material in four times, react at 85°C for 2min, add 15.9g of 1500 molecular weight perfluoropolyether carboxylic acid to the three-necked bottle in three times, stir and react for 30min to obtain the third mixed material. Then lower the temperature to room temperature, add 300ml of cyclohexane, stir for 10min, pour into a separating funnel and let stand for 24h, then take the lower layer of black liquid to obtain the organic phase containing nanomagnetic material;
[0073] S3. The organic phase containing the nano-magnetic material obtained in step S2 is placed in a 500mL three-necked flask, stirred at 450r / min and heated to 100°C, 65g of 1500 molecular weight perfluoropolyether oil is evenly added to the three-necked flask within 1min, stirred at 100°C for 10min, heated to 120°C, 11.5g of FC-4430 nonionic fluorinated surfactant is added to the three-necked flask in 4 portions, stirred at 120°C for 10min, heated to 165°C, and stirred at this temperature for 24h; the black liquid is quickly transferred to an ultrasonic constant temperature sealed reactor, and ultrasonic and shear dispersion are started at 165°C, with an ultrasonic frequency of 20kHz, a power of 200W, and a shear speed of 8500r / min, and ultrasonic shear dispersion is performed in the ultrasonic constant temperature sealed reactor for 5 hours. The rotation speed was reduced to 450 r / min, and the temperature was naturally reduced to room temperature. The mixture was poured into a 250 ml beaker and placed on a magnet for 60 h. After centrifugation at a speed of 5000 r / min for 40 min, the mixture was filtered using a 400-mesh filter cloth to obtain a brown-black fluoroether oil-based magnetic fluid.
[0074] Example 3
[0075] Formula: 37.0g FeCl 2 ·4H 2 O; 100.0 g FeCl 3 6H 2O; 150ml ammonia water; 3g oleic acid; 2.8g TSF-403 fluorine surfactant; 21.2g 2000 molecular weight perfluoropolyether carboxylic acid; 65g 2000 molecular weight perfluoropolyether oil; 10.8g FC5504 nonionic gemini fluorocarbon surfactant; 0.5g N-isopropyl-N-phenyl-p-phenylenediamine;
[0076] The preparation method comprises the following steps:
[0077] S1. Weigh 37.0g FeCl at room temperature 2 ·4H 2 O was dissolved in 60 ml of deionized water in a 100 ml beaker and set aside. 100.0 g of FeCl was weighed at room temperature. 3 6H 2 O in a 100ml beaker with 60ml deionized water for later use; measure 150ml ammonia water and put it in a 500ml three-necked bottle for later use; 2 Solution and FeCl 3 The solution was quickly mixed in a 200 ml beaker, and under the stirring condition of 500 r / min, the mixed solution was added into a three-necked bottle containing ammonia water at a uniform speed within 1 minute, and nitrogen was introduced for oxygen protection. After stirring for 5 minutes, a first mixed material was obtained; 0.5 g of N-isopropyl-N-phenyl-p-phenylenediamine was added to the three-necked bottle in 6 times, and the stirring reaction was continued for 5 minutes, and the temperature was raised to 85° C., and 3 g of oleic acid was added to the three-necked bottle at one time, and the reaction was stirred for 5 minutes to obtain a second mixed material;
[0078] S2. Add 2.8g of TSF-403 fluorine surfactant to the three-necked bottle containing the second mixed material in 5 times, react at 85°C for 2min, add 21.2g of 2000 molecular weight perfluoropolyether carboxylic acid to the three-necked bottle in three times, stir and react for 30min to obtain the third mixed material. Then lower the temperature to room temperature, add 300ml of cyclohexane, stir for 10min, pour into a separating funnel and let stand for 24h, then take the lower layer of black liquid to obtain the organic phase containing nanomagnetic material;
[0079] S3. Put the organic phase containing nanomagnetic material obtained in step S2 into a 500mL three-necked bottle, start stirring at 500r / min and heat to 100°C, add 65g 2000 molecular weight perfluoropolyether oil evenly to the three-necked bottle within 1min, stir at 100°C for 10min, heat to 120°C, add 10.8g FC5504 nonionic gemini fluorocarbon surfactant to the three-necked bottle in 5 times, stir at 120°C for 10min, heat to 165°C, stir at 30h; transfer the black liquid to an ultrasonic constant temperature sealed reactor quickly, start ultrasonic and shear dispersion at 165°C, ultrasonic frequency is 20kHz, power is 200W, shear speed is 10000r / min, ultrasonic shear dispersion is carried out in the ultrasonic constant temperature sealed reactor for 6 hours. Reduce the speed to 500r / min, and cool naturally to room temperature. The solution was poured into a 250 ml beaker and placed on a magnet for 72 hours. The solution was centrifuged at 5000 r / min for 60 minutes and then filtered using a 400-mesh filter cloth to obtain a brown-black fluoroether oil-based magnetic fluid.
[0080] Comparative Example 1
[0081] Comparative Example 1 is similar to Example 1, except that in step S2, no MS-7163 fluorine surfactant is added, and the other conditions are the same as those in Example 1.
[0082] Comparative Example 2
[0083] Comparative Example 2 is similar to Example 1, except that in step S3, no FC-403 nonionic fluorinated surfactant is added, and the other conditions are the same as those in Example 1.
[0084] Comparative Example 3
[0085] Comparative Example 3 is similar to Example 2, except that in step S2, no MS-7100 fluorine surfactant is added, and the other conditions are the same as those in Example 2.
[0086] Comparative Example 4
[0087] Comparative Example 4 is similar to Example 2, except that in step S3, no FC-4430 nonionic fluorinated surfactant is added, and the other conditions are the same as those in Example 2.
[0088] Comparative Example 5
[0089] Comparative Example 5 is similar to Example 3, except that in step S2, TSF-403 fluorine surfactant is not added, and the other conditions are the same as those in Example 3.
[0090] Comparative Example 6
[0091] Comparative Example 6 is similar to Example 3, except that in step S3, FC5504 nonionic gemini fluorocarbon surfactant is not added, and the other conditions are the same as those in Example 3.
[0092] Test example
[0093] (1) The fluoroether oil-based magnetic fluids prepared in Examples 1-3 were tested by transmission electron microscopy (TEM), X-ray diffractometer (XRD), infrared spectrometer (FT-IR), vibrating sample magnetometer (VSM), and rotational viscometer. The TEM test results are as follows: Figure 1 , Figure 5 , Fig. 9 The XRD test results are shown in Figure 2 , Figure 6 , Fig.10 As shown, the FT-IR test results are as follows Figure 3 , Figure 7 , Fig.11 As shown, the VSM test results are as follows Figure 4 , Figure 8 , Fig.12 The viscosity test results are shown in Table 1.
[0094] Table 1
[0095] Viscosity value (mPa.s) Example 1 1083 Example 2 2083 Example 3 3106
[0096] The viscosity test results in Table 1 show that the viscosity of the magnetic fluid obtained by using perfluoropolyether oil with different molecular weights as the base liquid is also different.
[0097] Depend on Figure 1 , Figure 5 , Fig. 9 It can be seen from the TEM spectrum that the nano-magnetic cores in the perfluoropolyether oil-based magnetic fluid have uniform particle sizes, distinct boundaries, and no large-scale agglomeration between the magnetic cores, showing a nearly circular shape. The average particle size is about 10-30nm. Figure 2 , Figure 6 , Fig.10 As shown, there are very obvious diffraction peaks at 18.36°, 30.13°, 35.02°, 42.74°, 53.62°, 57.18°, and 62.37°, and the peak values are (111), (220), (311), (400), (422), (511), and (440), respectively. By comparing Fe 3 O 4 Standard spectrum (JCPDS19-0629 card), its crystal structure is inverse spinel structure, and its purity is high. Figure 3 , Figure 7 , Fig.11 The fluorocarbon functional group shown has been attached to the Fe 3 O4 The surface of magnetic powder. VSM test results are as follows Figure 4 , Figure 8 , Fig.12 As shown, the fluoroether oil-based magnetic fluids prepared in the three examples have relatively good superparamagnetism, and the specific saturation magnetization is about 20emu / g. The specific saturation magnetization of the magnetic fluids in the examples and comparative examples is shown in Table 2.
[0098] (2) The magnetic fluids obtained in Examples 1-3 and Comparative Examples 1-6 were tested for anti-sinking properties. The anti-sinking property test process of the magnetic fluid was as follows: 20 ml of the magnetic fluid was placed in a 50 ml beaker, and the beaker was placed on an N42 magnet with an area larger than the bottom of the beaker. After standing for 90 days, the specific gravity of the upper layer of the magnetic fluid in the beaker was tested. The difference between the original specific gravity and the current specific gravity was the reference value for anti-sinking properties. The smaller the value, the better the anti-sinking properties. The test results are shown in Table 2.
[0099] Table 2
[0100]
[0101]
[0102] According to the experimental results of 3 groups of examples and 6 groups of comparative examples, the difference in specific saturation magnetization, specific gravity and anti-settling property of magnetic fluid when using single fluorinated surfactant for grafting modification and dispersion is very obvious compared with using double fluorinated surfactant for grafting modification and dispersion. This shows that the double fluorinated surfactant modified connection structure (double bridge structure) can make the magnetic powder dispersed better in perfluoropolyether oil, and even after being left in the magnetic field for 90 days, the magnetic properties can be kept unchanged.
[0103] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing a perfluoropolyether oil-based magnetic fluid, characterized in that: The following steps are involved: S1. Fe3O4 nanoparticles were prepared by chemical coprecipitation, and a first mixed material was obtained after the reaction was completed. The first mixed material was mixed with an antioxidant and oleic acid and reacted to obtain a second mixed material; S2. The second mixture is mixed with a fluorinated surfactant and a perfluoropolyether carboxylic acid and reacted to obtain a third mixture, and the third mixture is extracted with an organic solvent and phase-transferred to obtain an organic phase containing a nano-magnetic material; S3. The organic phase containing the nano-magnetic material is mixed with a non-ionic fluorinated surfactant and a perfluoropolyether oil and reacted to obtain the perfluoropolyether oil-based magnetic fluid.
2. The method for preparing a perfluoropolyether oil-based magnetic fluid according to claim 1, characterized in that: Include at least one of the following features: (1) The antioxidant includes N-isopropyl-N-phenyl-p-phenylenediamine 、 At least one of N-phenyl-β-naphthylamine and N-N'-diphenyl-p-phenylenediamine; (2) The fluorine surfactant includes at least one of MS-7163 fluorine surfactant, MS-7100 fluorine surfactant, and TSF403 fluorine surfactant; (3) The perfluoropolyether carboxylic acid comprises at least one of a 1000 molecular weight perfluoropolyether carboxylic acid, a 1500 molecular weight perfluoropolyether carboxylic acid, and a 2000 molecular weight perfluoropolyether carboxylic acid; (4) The nonionic fluorinated surfactant includes at least one of FC-403 nonionic fluorinated surfactant, FC-4430 nonionic fluorinated surfactant, and FC5504 nonionic gemini fluorocarbon surfactant; (5) The perfluoropolyether oil comprises at least one of a 1000 molecular weight perfluoropolyether oil, a 1500 molecular weight perfluoropolyether oil, and a 2000 molecular weight perfluoropolyether oil.
3. The method for preparing a perfluoropolyether oil-based magnetic fluid according to claim 1, characterized in that: In step S1, the preparation of the nano-Fe3O4 magnetic particles by the chemical coprecipitation method comprises the following steps: The aqueous solution containing the divalent iron salt and the trivalent iron salt is mixed with the precipitant under stirring, and an inert gas is introduced to perform oxygen removal protection, and stirring is continued until the reaction is completed to obtain the first mixed material.
4. The method for preparing a perfluoropolyether oil-based magnetic fluid according to claim 1, characterized in that: In step S1, the step of obtaining the second mixed material includes: adding the antioxidant to the first mixed material in 4-6 times, stirring and reacting for 4-6 minutes, heating to 80-90°C, adding oleic acid, and continuing to stir and react for 4-6 minutes to obtain the second mixed material.
5. The method for preparing a perfluoropolyether oil-based magnetic fluid according to claim 1, characterized in that: In step S2, the step of obtaining the third mixed material comprises: adding the fluorinated surfactant to the second mixed material in 3-5 times, stirring and reacting at 80-90° C. for 2-3 minutes, then adding the perfluoropolyether carboxylic acid, and continuing to stir and react for 30-35 minutes to obtain the third mixed material.
6. The method for preparing a perfluoropolyether oil-based magnetic fluid according to claim 1, characterized in that: In step S2, the step of transferring the extraction phase includes: adding cyclohexane to the third mixed material, stirring and mixing, pouring into a separating funnel and letting it stand, and taking out a layer of black liquid, which is the organic phase containing the nano-magnetic material.
7. The method for preparing a perfluoropolyether oil-based magnetic fluid according to claim 1, characterized in that: The reaction process in step S3 specifically includes: under stirring, heating the organic phase containing the nanomagnetic material to 98-102° C., adding perfluoropolyether oil and stirring for 8-12 minutes, heating to 120-125° C., adding non-ionic fluorinated surfactant in 3-5 portions, stirring for 10-15 minutes, heating to 160-170° C., and stirring for 20-30 hours.
8. The method for preparing a perfluoropolyether oil-based magnetic fluid according to claim 1, characterized in that: The mass ratio of the oleic acid, the fluorine surfactant, the perfluoropolyether carboxylic acid, the nonionic fluorine-containing surfactant and the perfluoropolyether oil is 2.8-3.2: 2.3-3.2: 10.6-21.2: 9.5-11.5: 60-70.
9. The method for preparing a perfluoropolyether oil-based magnetic fluid according to claim 1, characterized in that: In step S3, after the reaction is completed, an ultrasonic shear dispersion and separation step is also included, specifically including starting ultrasound at 160-170°C, and ultrasonic shear dispersion at a speed of 7000-10000 r / min for 4-6 hours, reducing the speed to 400-500 r / min, placing it on a magnet for 48-72 hours after cooling, and obtaining the perfluoropolyether oil-based magnetic fluid after centrifugal separation and filtration.
10. A perfluoropolyether oil-based magnetic fluid, characterized in that: The magnetic fluid is prepared by the method for preparing the perfluoropolyether oil-based magnetic fluid described in any one of Examples 1-9.